METHOD OF FORMING INDIVIDUAL PROPHYLAXIC PROGRAMS USING EXTENDED ANAMNESTIC APPLICATION IN THE CONDITIONS OF THE WORK OF THE MEDICAL INFORMATION SYSTEM IN HOSPITAL - Gandzyuk V.А. (World of Medicine and Biology, 2018)
The article shows the results of implementation of the improved anamnesis questionnaires in the single medical information system of the health care institution with the aim of forming individual preventive programs. The introduction of this development will allow introducing monitoring and evaluation of risk factors for the development of noncommunicable diseases and a list of justified diagnostic examinations, is the basis for planning the necessary volumes of preventive interventions. Wide use of the capabilities of the medical information system will allow making informed management decisions, conducting their analysis and rationally using the resources of the health care institution.